A rare case of steroid cell tumor of ovary: case report - ., Sharanya; Peter, Monalisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Steroid cell tumors of the ovary account for less than 0.1% of all ovarian tumors. These tumors may present at any age with presentations related to the hormonal activity and virilizing properties of tumor. A 61-year-old postmenopausal women presented with complaints of postmenopausal bleeding for 15 days. Parity score of P3L3, not tubectomised. Menopaused 16 years back. History of weight loss noted. She is a known case of diabetes mellitus for 6 years not on any treatment and a known case of depressive disorder for 35 years on treatment on trihexphenidyl lurasidone. Had undergone sigmoid colon polyp removal in June 2018. On examination, P/A- mild gaseous distension (+). P/S- cervix flushed with vagina, pulled up cervix. P/V- uterus size and position couldn’t be made out, anterior fornix fullness (+). Ultrasonography showed bulky uterus with fibroid 4x4cm, endometrial thickness- 9 mm? Krukenberg tumor and posterior mediastinal lymph nodes. Patient underwent Total abdominal hysterectomy with bilateral salpingo-oophorectomy with frozen section on 01/07/19. Frozen section: 1. Ovaries: right ovary - fibrothecoma, left ovary- simple cyst. 2. Uterus- endometrial hyperplasia with atypia. 3. Myometrium- leiomyoma and adenomyosis. Postoperative period was uneventful. On microscopic examination, impression: right ovary- steroid cell tumor, uterus-endometrial hyperplasia with cytological atypia. Ovarian steroid cell tumors are grouped under sex chord stromal tumors and are usually benign, unilateral and characterized by a steroid cell proliferation. Steroid cell tumors are associated with androgenic changes with variable frequency, ranging from 12% to over 50% respectively. The primary treatment is surgical extirpation of the primary lesion and there are no reports of effective radiation or chemotherapy. In a young patient with stage IA disease, a unilateral salpingo oophorectomy is adequate.